An analysis of nature-based treatment processes for cleaning contaminated surface water runoff from an informal settlement: a case study of the Stiebeuel River catchment, Franschhoek, South Africa - Nicklin, Emily (Department of Environmental and Geographical Science, 2023)
Contaminated surface water runoff from inadequate drainage and sanitation systems in informal settlements threaten the quality of available freshwater and can negatively impact both human and environmental health. Biofiltration systems (biofilters) provide water pollution controls without inputs of additional energy and chemicals, placing them in the overall context of the need for affordable and sustainable stormwater infrastructure in informal settlements. In addition, cleaned waters from biofilters may be suitable for some reuse applications if they are well-designed and maintained. However, most research is conducted in developed countries where heavy metals are the main surface water pollutant. Consequently, little is known about the extent to which biofilters can be used to meet the water quality targets in conditions likely to be found in informal settlements. In addition, no attempts have been made to recover or reuse the surface water runoff from informal settlements, despite its high nutrient loadings. This study analyses the extent to which biofilters can be used to clean and reuse contaminated surface water runoff from informal settlements. The objectives are threefold: (i) to analyse the performance of two field-scale biofiltration cells (one vegetated and one non-vegetated) that are batch-fed with surface water runoff from an upstream informal settlement; (ii) to determine the effects of varying operating, design and environmental parameters on the performance of the cells; and (iii) to develop a model which predicts the outflow pollutant concentrations under varying conditions. Both cells effectively reduced ammonia (NH3), Total Phosphate (TP) and Escherichia coli (E. coli) concentrations, but leached nitrate (NO3 - ) and nitrite (NO2 - ). The treated waters were suitable for irrigational reuse, however, additional disinfection was required to reduce faecal contamination in some cases. Correlation analyses showed that inflow water quality significantly influenced cell performance, with the vegetated cell outperforming the non-vegetated cell under higher inflow pollutant concentrations. Multiple regression models also investigated several parameters influencing outflow NH3 and showed that inflow pH, temperature and NH3 concentration can be used to determine the outflow NH3 concentration of the cells. These models are important for predicting cell performance and thus can be used to improve the design and/or operation of the cells for varying inflow water quality conditions.